AKTIVITAS ENZIM LIGNOSELULASE INOKULAN YANG DIPRODUKSI DARI BERBAGAI TINGKAT PENGGUNAAN CACING TANAH (Lumbricus rubellus) - K. D., Kusumajaya; Mudita, I M.; Sutama, I N. S. (Jurnal Peternakan Tropika, 2016)
This study aimed to evaluate the effect of the use of earthworms to the activity of the enzyme lignoselulase of inoculants and best use of earthworms levels capable of producing an inoculant with the highest enzyme activity. This research was conducted at the Laboratory of Animal Nutrition and Feed Faculty of Animal Husbandry Universitas Udayana for 3 months. The Research using a completely randomized design (CRD) 4 treatments and 3 replications. Treatments were inoculant are produced using 0.1% of earthworm (BC1), inoculant are produced using 0.2% of earthworm (BC2), inoculant are produced using 0.3% of earthworm (BC3) and inoculant are produced using 0.4% earthworm (BC4). The variables were observed in this study was the enzyme activity of lignase, cellulase and xylanase in four periods of 30 minutes, 1 hour, 2 hours and 3 hours of incubation. The results showed that the increased use of earthworms from 0.1% to 0.2 to 0.4% in the production of inoculant can increase enzyme activity lignase, cellulase, and xylanase in each period of time incubation. The use of 0.4% earthworm level (BC4) was able to produce highest and significantly different (P <0.05) of lignase, cellulase and xylanase enzyme activity at each time of incubation (except for cellulase enzyme activity at 3 hours incubation) compared with BC1. Based on the results research concluded that the increase of level earthworm can produce inoculant with higher lignocellulase enzzime activity and use 0.4% of earthworm can produce inoculant with highest lignase, cellulase and xylanase enzyme activity compared to others inoculant.
Keywords: Earthworm, Lignocellulase Enzyme Activity, Incubation Periods, Inoculant.